Construction of Trust Relationship between Doctors and Patients: A Social Psychological Analysis - Li, Liangyue; Zhai, Fangming; Liu, Hailan; Wan, Chonghua; Tan, Jianfeng; Zeng, Libin (Environment and Social Psychology, 2021)
Doctor-patient trust is the basis of harmonious doctor-patient relationship. Social psychology plays a unique role in interpreting the connotation and construction of doctor-patient trust relationship. From the two levels of doctor-patient interpersonal trust and intergroup trust, this paper summarizes the relevant theoretical viewpoints of social psychology on the construction of doctor-patient trust relationship, and analyzes the key factors affecting doctor-patient interpersonal trust and intergroup trust. On this basis, this paper puts forward the construction path of doctor-patient trust of “interpersonal interaction-emotional communication-interpersonal trust” and “intergroup interaction-social knowledge-intergroup trust”, reveals the interaction mechanism of interpersonal trust and intergroup trust and the circular feedback mechanism between them to promote the formation of doctor-patient trust relationship, and establishes a social psychology model of the formation mechanism of doctor-patient trust relationship.